IMAGE IN THE PREDIGITAL AGE THE CULTURE OF IMAGE IN THE CYBERNETIC SYSTEM. - MORITZ, Eugen (REVART: Specialized Review of Theory & Critique of Arts, 2015)
The digital world, in conceptual meaning, is the result of art, science and technology, evolution, which began in the 19th century and continued into the late twentieth century. From painting to "home page" we have a whole production of technical images, static and moving, that constitutes the artistic thinking in pictures, to our local and global existence. Lodged in a production of images, this image of the technical world destroy the classical forms of knowledge and representation of reality, redefining our reporting from the real world or a virtual (virtual).